PROFIL PEREMPUAN DURHAKA DAN SALIHAH DALAM Q.S. AL-TAHRIM [66]: 10-12 - Desri Nengsih (Institut Agama Islam Negeri (IAIN) Keiri, 2020)
This paper discusses the study of disobedient and pious women in QS. Al-Tahrim [66]: 10- 12. It is limited to the letter and three verses because these three verses specifically tell about female characters. The purpose of this paper is to obtain a clearer and deeper interpretation of these verses so that a comprehensive understanding of the verse content is obtained. In addition, it is also to find out the typical women mentioned in the verse and the characteristics attached to them so that they deserve to be mentioned as typical for which class of women. From the results of the studies that have been carried out and also moving on from the interpretations of the verse, it is found that in verses 10-12 there are two typical women. First, the disobedient woman mentioned in verse 10. In this verse, it tells of two wives of the Prophet, namely Noah and Lut, who betrayed her husband and did not justify her husband's prophetic message, but said that her husband was crazy and leaked the secret of the arrival of guests. guest (angel) of her husband to his people. As a result of this action, Allah placed in hell with his people even though they were wives of the Prophets. Second, pious women, as seen from verses 11-12. In this verse, it tells about the faith of Asiyah, the wife of Fir'aun and also talks about Maryam who always worships and keeps her honor.